Bladder Leiomyomatosis: A Case Report - Farazestanian, Marjane; Yousefi, Zohreh; Mofrad, Malihe H.; Seresht, Leila Mousavi; Jafarian, Amir Hosein; Moeindarbari, Somayeh (Current Women's Health Reviews, 2021)
Introduction: Bladder leiomyoma, commonly found in middle-aged females, is a rare, benign, and mesenchymal tumor of the bladder. Its incidence rate is lower than 0.5% of all types of bladder tumors. There are fewer than 250 reports on bladder leiomyoma. Herein, we report a case of bladder leiomyoma in 37 years’ female. Case Presentation: A 37-year-old multiparous woman has been presented with complaints of occasional hematuria and dysuria and irritative symptoms. In the examination and imaging, a mass with a size of 8 cm was reported in the anterior border of the uterus with a firm consistency. Surgery was performed, and the mass was resected. Postoperative histopathology review confirmed bladder leiomyoma. Conclusion: Leiomyoma should be considered as a differential diagnosis in women presenting with dysuria, frequency or hematuria and a firm consistency mass even in the unusual site as the bladder. Complete resection leads to a very good outcome with almost no recurrence.
Keywords: hematuria